PERAN PERBANKAN SYARIAH DALAM MENINGKATKAN KEWIRAUSAHAAN BAGI USAHA MIKRO DI MUARO BUNGO (Studi Pada Bank Syariah Indonesia KCP Muaro Bungo) - Biesriani Biesriani; Arsa Arsa; Awal Habibah (UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to determine and analyze the role of Sharia banking in increasing micro business entrepreneurship in Muaro Bungo, describe the obstacles and solutions of Bank BSI KCP Muaro Bungo in increasing entrepreneurship for micro businesses in Muaro Bungo, and find out and analyze Islamic views regarding sharia banking in increasing entrepreneurship for micro businesses in Muaro Bungo. The research method used is a qualitative descriptive approach, with data collection techniques through interviews, observation, and documentation. The results of the study show that BSI KCP Muaro Bungo has a strategic role in three forms of financing, namely: (1) sharia working capital financing, such as the provision of funds for business capital, stock of goods, and employee salaries; (2) sharia investment financing in the form of investment and rental of capital goods; and (3) consumptive financing to support business operations, such as vehicles and work tools through purchase and sale contracts, hire purchases, and cooperation. The obstacles faced include limited collateral, high risk in financing returns, and low public understanding of the Islamic financial system. The solutions implemented include the use of government financing programs, business potential assessments, and public education. The Islamic view on Shariat banking in enhancing entrepreneurship is based on Al-Quran, Sunnah, and ijtihad, by emphasizing the principles of justice, transparency, and blessings, as well as avoiding the practice of usury, ambiguity of contracts, and prohibited businesses.